Developing and Maintaining Implementation of a Teaching-for-Thinking Program - Adey, Philip; Edmiston, Alan (Columbus, OH : ERIC Clearinghouse for Science, Mathematics, and Environmental Education, 2001)
This chapter describes an inservice Professional Development (PD) program for introducing a cognitive acceleration course designed to enhance students' higher order thinking capabilities. Teaching for thinking requires a specialized set of understandings and techniques, and the standard PD program described here lasts for two years and includes both center-based days and in-school coaching. The principles upon which this standard program is based and a variety of alternative modes of delivery using teacher leaders are explored. While maintaining the same basic principles of the program, modes of delivery are adapted to suit particular contexts. (Contains 21 references.) (Author)
Availability: ERIC Clearinghouse for Science, Mathematics, and Environmental Education, 1929 Kenny Road, Suite 200, Columbus, OH 43210-1080. Tel: 800-276-0462 (Toll Free); Fax: 614-292-0263; Web site: http://www.ericse.org.
ERIC Note: In: Developing Teacher Leaders: Professional Development in Science and Mathematics; see ED 451 031.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Cognitive Development; Critical Thinking; Elementary Secondary Education; Faculty Development; Teacher Improvement; Teachers; Reports, Descriptive